THE PORTRAYAL OF HARMONIOUS SOCIETY AND GOOD GOVERNMENT IN CONFUCIUS (2010) MOVIE BY HU MEI - Ahmad Faqih (Universitas Airlangga, 2020)
Confucianism strongly emphasizes the principles of humanism, morals and ethics to guide humanity in realizing the meaning and purpose of life. More broadly, the principles of Confucianism about humanism, morality will form good social relations and create a peaceful and prosperous life. This article tries to figure out the significance relationship between society and government in creating peaceful human life. As in Confucianism peace itself is created through harmonious social relations in plural social conditions and under good governance. It is important to understand the concept of harmonious society as taught by Confucius by looking at the practice of community relations and a government. The findings of this study are a condition of a harmonious society will be formed when the authorities emphasize the principles of the teachings of humaneness, morality and ethics in regulating government and society. Mutual understanding between government and society through non-exclusionary relationship is also an indicator in achieving harmony and peaceful life.